Antibodies against MLC1 found in patients with NMOSD-like disease mediate astrocytopathy in rodent models - Hoi Kiu Wong; Samantha Ho; Qian Yu; Katherine S. Given; Dorina Shqau; Selia Baier; Stephan Winklmeier; Heike Rübsamen; Arek Kendirli; Kathrin Schanda; Eva Oswald; Katharina Bräuer; et al. (Science Translational Medicine, 2026)
The identification of autoantibodies against aquaporin-4 (AQP4) and myelin oligodendrocyte glycoprotein (MOG) has been essential in distinguishing neuromyelitis optica spectrum disorder (NMOSD) and MOG antibody–associated disease (MOGAD) from classical multiple sclerosis (MS), with important implications for treatment. However, for several patients within this disease spectrum, the target of the autoimmune response remains unknown. Here, we describe the modulator of VRAC current 1 (MLC1), a membrane protein with extracellular epitopes enriched at astrocytic end feet, as an autoantigen. Serum MLC1 antibodies were verified with a cell-based assay, identifying four MLC1 immunoglobulin G (IgG)–positive patients among 297 patients with inflammatory autoimmune diseases of the central nervous system who were screened. All four MLC1 IgG–positive patients exhibited overlapping yet atypical clinical features of MS and NMOSD and tested negative for AQP4 and MOG antibodies. Moreover, treatment with a monoclonal MLC1 antibody induced astrocytopathy in mouse cerebellar slice cultures and in a rat encephalitis model. Thus, MLC1 antibodies identify a subset of patients with an NMOSD-like phenotype, underscoring their potential as a disease marker with pathogenic relevance.